Dynamic transmit antenna shuffling scheme for MIMO wireless communication systems - Chong, Jin Hui; Ng, Chee Kyun; Noordin, Nor Kamariah; Mohd Ali, Borhanuddin (Springer, 2012)
Two novel dynamic transmit antenna shuffling schemes, namely ‘Optimal’ and ‘Max STBC’, are presented in order to reduce the interference in V-BLAST/STBC scheme. These antenna shuffling schemes with the channel state information (CSI) from the receiver, which significantly improves performance of the MIMO system in Rayleigh flat-fading channels by selecting the appropriate antenna shuffling pattern, have been compared with a few other related schemes in terms of BER and system capacity. The ‘Optimal’ antenna shuffling scheme improves the BER performance significantly with a gain of 2 dB at BER of 10–3 compared to all other schemes, while the ‘Max STBC’ antenna shuffling scheme enhances the V-BLAST/STBC system capacity by 4%.